Spatial Development of the Dipolarization Region in the Inner Magnetosphere. Issue 7 (17th July 2018) - Ohtani, S.; Motoba, T.; Gkioulidou, M.; Takahashi, K.; Singer, H. J.
Abstract: The present study examines dipolarization events observed by the Van Allen Probes within 5.8  R E from Earth. It is found that the probability of occurrence is significantly higher in the dusk‐to‐midnight sector than in the midnight‐to‐dawn sector, and it deceases sharply earthward. A comparison with observations made at nearby satellites shows that dipolarization signatures are often highly correlated (c.c. >0.8) within 1 hr in magnetic local time (MLT) and 1  R E in R XY, and the dipolarization region expands earthward and westward in the dusk‐to‐midnight sector. The westward expansion velocity is estimated at 0.4 hr (in MLT) per minute, or 60 km/s, which is consistent with the previously reported result for geosynchronous dipolarization. The earthward expansion is apparently less systematic than the westward expansion. Its velocity is estimated at 50 km/s (0.5  R E /min), comparable to the westward expansion velocity, but it is suggested that the earthward expansion slows down as the dipolarization region approaches Earth, and it eventually stops. This idea is consistent with the earthward reduction of the occurrence probability of dipolarization events. Whereas this earthward expansion is difficult to explain with the conventional wedge current system, it may be understood in terms of a current system with two wedges, one with the R1 polarity outside and the other with the R2 polarity closer to Earth. For such a current system the region of dipolarization is confined in radial distance between the two wedge currents, and it is considered to expand earthward as the R2‐sense wedge moves earthward along with injected plasma. Key Points: The occurrence probability of dipolarization in the inner magnetosphere is significantly skewed duskward, and it decreases sharply earthward The dipolarization region expands westward at 0.4 hr/min in MLT and earthward at 0.5  R E /min on average in the dusk‐to‐midnight sector The azimuthal velocity is comparable to that of geosynchronous dipolarization, but the earthward velocity is significantly slower